Nanoparticles in wastewater: A comprehensive approach to understanding their ecotoxicity and genotoxicity - Nina Doskocz; Katarzyna Affek; Magdalena Matczuk; Marcin Drozd; Monika Załęska-Radziwiłł (Desalination and Water Treatment, 2025)
Herein, we investigated the impact of wastewater-borne Al₂O₃ nanoparticles (Al₂O₃NPs) on the aquatic organism Daphnia magna, focusing on both ecotoxicity and genotoxicity. The widespread use of nanoparticles (NPs) in various industries has raised concerns about their environmental effects, especially in wastewater. Our findings showed that exposure to Al₂O₃NP-containing wastewater, even after biological treatment, led to significant immobilization and reduced reproduction of D. magna. Additionally, changes in the genetic material of crustaceans were identified using RAPD-PCR (Random Amplified Polymorphic DNA) and TEM (Transmission Electron Microscopy), which revealed NP aggregates in the intestines, indicating the digestive tract as the primary site of NP uptake and possible cellular dysfunction. The hydrodynamic size of NPs increased post-treatment, and zeta potential measurements suggested a tendency for the nanomaterials to agglomerate. The concentration of dissolved aluminum ions also rose significantly after one day of biological wastewater treatment. These findings highlight the considerable risks wastewater-borne NPs pose to aquatic ecosystems and underscore the need for effective monitoring and risk management strategies to mitigate their environmental impact.